2012
DOI: 10.1088/0957-0233/23/3/035201
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of ICCD detectors and optimized 2D phosphor thermometry

Abstract: This paper presents investigations on the limitations of intensified CCD (ICCD) cameras when performing quantitative 2D temperature measurements using thermographic phosphors. The temperature is evaluated using a two-color ratio technique, which demands high signal linearity of the detector. However, this work shows that the ICCD cameras used suffer from nonlinearity at levels of irradiance that do not necessarily produce particularly high count levels, i.e. well below the saturation limit of the A/D converter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
(14 reference statements)
0
14
0
Order By: Relevance
“…They can be a major issue for quantitative measurements based on light intensity (Lindén et al 2012). The camera response to light irradiance was therefore characterized for different amplification gains (i.e., different voltages applied between the input and the output of the MCP).…”
Section: Linearity Of the Detection Chainmentioning
confidence: 99%
“…They can be a major issue for quantitative measurements based on light intensity (Lindén et al 2012). The camera response to light irradiance was therefore characterized for different amplification gains (i.e., different voltages applied between the input and the output of the MCP).…”
Section: Linearity Of the Detection Chainmentioning
confidence: 99%
“…All measurements described in the present study were performed without applying the microchannel plate (MCP) normally serving to intensify the signals, because the results of some previous studies 26,27 had shown that this part of the device had been responsible for nonlinear response of ICCDs. To avoid confusion, from now on, we shall denote our detection device by CCD (instead of ICCD).…”
Section: Methodsmentioning
confidence: 99%
“…ICCD sensors have image intensifiers in front of the sensor to boost the number of incoming photons [ 102 ]. This improves sensitivity in low-light scenarios at the cost of a higher supply voltage (1 kV) and reduced dynamic range [ 103 , 104 ]. EMCCD sensors have a similar gain performance to ICCD.…”
Section: Detection Setups and Optical Sensor Technologymentioning
confidence: 99%